Correlações quânticas e transição quântico-clássica em cavidades ópticas - Rossatto, Daniel Zini (2014)
This thesis consists of three studies in the context of cavity quantum electrodynam- ics. Firstly, we investigate the quantum-to-classical transition of a dissipative cavity .eld by measuring the correlations between two non-interacting atoms coupled to the cavity mode. We note that there is a time window in which the mode presents a classical be- havior, which depends on the cavity decay rate, the atom-.eld coupling strength and the number of atoms. Then, considering the steady state of two atoms inside the cavity, we note that the entanglement between the atoms disappears while the intracavity mean number of photons (ñ) increases. However, the mutual information, the classical corre- lations and the quantum discord reach asymptotic non-zero values even in the limit of (continue...)